Causes of Divorce among Middle-Aged Couples: A Study at the Syariah Court of the Federal Territory of Kuala Lumpur - Sallehuddin, Nur Syazwani; Mat Hussin, Mohd Norhusairi (Kanun: Jurnal Undang-undang Malaysia, 2025)
Divorce among middle-aged couples has been a focal point of discussion in the media reports and academic research. Various factors contribute to the occurrence of divorce among middle-aged couples in Malaysia. This study was conducted to analyse the causes of divorce among middle-aged couples aged 40-60 at the Syariah Court of the Federal Territory of Kuala Lumpur (MSWP KL). Employing a qualitative approach, the study utilised appropriate data collection and analysis methods to achieve its stated objectives. Data collection was carried out through library research, interviews, and case studies, while the data obtained were analysed thematically and descriptively. The study identified several contributing factors to divorce among middle-aged couples in the Syariah Court of Kuala Lumpur, such as a lack of mutual understanding, issues related to the attitude and character of spouses, neglect of financial responsibilities (nafkah), religious factors, third-party interference, and the challenges associated with aging. As a resolution, the study proposed several recommendations to address and mitigate the prevalence of divorce in this demographic. Keywords : Divorce, dissolution of marriage, causes of divorce, factors of divorce, Syariah Court of the Federal Territory of Kuala Lumpur, middle-age Full Text :  PDF